Koncepcja miłości a wątki homoerotyczne w twórczości literackiej Michaiła Kuzmina i Karola Szymanowskiego - Kral, Wojciech (Przegląd Rusycystyczny, 2006)
THE CONCEPT OF LOVE AND HOMOEROTIC MOTIFSIN THE WRITINGS OF MIKHAIL KUZMI N AND KAROL SZYMANOWSKI Summary The article compares the themes of love and eroticism in the works of Mikhail Kuzmin and KarolSzymanowski, an outstanding Polish composer and amateur writer. In Szymanowski™s major workof literature Ephebos there are similarities to Kuzmin™s work that cannot always be attributed toboth artists™ homosexual orientation, and that are not limited to the erotic themes. Given the presen-ce of references to Plato™s philosophy, the image of wings, as well as thematic references to antiqu-ity and Byzantium in the work of both writers, we can hypothesize that Szymanowski was familiarwith Kuzmin™s writing.